Affect perception as a cognitive function: Validity and clinical application of a neuropsychological test battery in healthy individuals and patients with brain lesions - Χίου, Καλλιόπη; Βάγια, Αργυρώ; Χαριτίδου, Ελένη; Καρακώστας, Δημήτρης; Κοσμίδου, Μαρία-Ελένη (Psychology: the Journal of the Hellenic Psychological Society, 2020)
The abstract is available in the PDF